Volatility Spillovers Effects between Energy Commodities and Islamic Stock Markets - Mehmet Hüseyin Bilgin; Gülin Vardar; Berna Aydoğan; Evan Lau (Asian Academy of Management Journal of Accounting and Finance, 2024)
Empirical research exploring the relationship between capital markets and energy prices plays a crucial role in shaping policies for the growth of the Islamic financial system. This study aims to investigate potential shock transmission and volatility spillover effects among Islamic stock indices from selected Middle East and Northern Africa countries as well as crude oil prices and natural gas, over the period from August 2007 to September 2020. Applying VAR-BEKK-GARCH representation, the results reveal the evidence of bidirectional cross-market shock and volatility spillover effects between Kuwait and Qatar Islamic stock indexes, crude oil prices, and natural gas. Moreover, the results indicate the existence of bidirectional/unidirectional shock and volatility spillovers between Islamic indexes and all other variables, meaning there are information flows between these variables in all four countries except Turkey. Regarding the results of volatility spillovers, there is no spillover effect between Turkey’s MSCI Islamic index and Brent crude oil. These findings bear significant implications for portfolio management, offering valuable insights to financial market participants for making improved portfolio allocation decisions. Also, comprehending the volatility transmission mechanism across these markets is vital to provide policymakers and regulatory authorities with insight into the impact of energy prices on Islamic stock markets.